2006
DOI: 10.1111/j.1530-0277.2006.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Outlet Densities Affect Violence Rates

Abstract: Assault rates were most strongly related to median household incomes and minority populations within zip code areas. Controlling for changes in assault rates related to these measures, greater numbers of licensed alcohol retail establishments, especially bars and off-premise outlets, were related to rates of assault. Failures to regulate the growth in numbers of bars will increase rates of violence, especially in urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
181
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(206 citation statements)
references
References 14 publications
21
181
1
3
Order By: Relevance
“…These findings are consistent with a body of research that has shown that the presence and density of alcohol outlets are associated with violent crime in cities with a population 200,000 or greater in the US. 9,10,14,[27][28][29][30][31][32][33] For example, a study in Washington DC found that community-level liquor outlet density was significantly associated with violent crimes, independent of other neighborhood factors including violent crime, and the prevalence of weapons and illicit drugs. 21 Another study in Los Angeles, found that the total liquor outlet density was positively related to the assault rate (one type of violent crime) over the study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with a body of research that has shown that the presence and density of alcohol outlets are associated with violent crime in cities with a population 200,000 or greater in the US. 9,10,14,[27][28][29][30][31][32][33] For example, a study in Washington DC found that community-level liquor outlet density was significantly associated with violent crimes, independent of other neighborhood factors including violent crime, and the prevalence of weapons and illicit drugs. 21 Another study in Los Angeles, found that the total liquor outlet density was positively related to the assault rate (one type of violent crime) over the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Studies generally find that off-premise outlets are better predictors of crime than on-premise alcohol outlets. 10,13,19,20 Unlike bars and restaurants, offpremise alcohol outlets can sell alcoholic beverages in large quantities, which can be consumed in uncontrolled environments (e.g., motor vehicles, outside the outlet, and home). 20 In bars and restaurants, servers control how much patrons receive and can stop serving patrons if they appear intoxicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is highly relevant to public health because there is considerable evidence that problems such as intentional injuries (Cunradi et al, 2012;Gruenewald & Remer, 2006;Livingston, 2008Livingston, , 2011Mair et al, 2013;Toomey et al, 2012), road trauma (McMillan et al, 2007;Ponicki et al, 2013), and child abuse and neglect (Freisthler & Weiss, 2008;Freisthler et al, 2007) occur more frequently in areas with more alcohol outlets (Campbell et al, 2009). Exposure to outlets may therefore contribute to health disparities between these racial and ethnic minorities and the White majority population and may be an appropriate target for preventive intervention (Romley et al, 2007).…”
Section: P Revious Studies Have Found That Areas In the Unitedmentioning
confidence: 99%
“…Studies have found associations between the density of alcohol outlets and various alcohol-related health outcomes, suggesting that limiting opportunities to buy alcohol reduces consumption and its adverse effects [26,27]. And limiting underage alcohol access reduces alcohol consumption and alcohol-related health outcomes in youth [28].…”
Section: Alcoholmentioning
confidence: 99%